Understanding The Important Role of Decision-Making in Enhancing Organisational Effectiveness: Concepts, Processes, and Managerial Responsibilities - Saleh, Nor Shela; Rosli, Mohd Shafie; Isa, Khairunesa; Abu Bakar, Thuaibah; Md. Ali, Azlah (JBS Nexus, 2025)
The decision-making process is a fundamental aspect of organizational management. It involves various stakeholders, and the outcomes can have significant implications for finances, individuals’ lives, and the larger economy, resulting in both positive and negative repercussions. Errors in decision-making can lead to a range of adverse consequences, including reduced profits, incurred losses, and even impacts on the national economy. This study is conceptual in nature, focusing on the discussions and perspectives of previous researchers regarding decision-making within organizations. The primary aim is to explore the concepts, processes, and roles of managers in the decision-making process. The findings suggest that decision-making is a multifaceted process that involves different levels of management, including top, middle, and lower-level managers. The researcher also examines the rationalization of decision-making, emphasizing its critical components as well as its inherent weaknesses. To ensure consistency and adherence to proper procedures, the decision-making process must be executed effectively and efficiently. This is especially crucial for managers, who play a vital role in shaping various aspects of the organization. Three key elements define the role of managers in decision-making: rationality, bounded rationality, and intuition. A blend of these approaches is essential for achieving and maintaining the organization’s mission and vision, thereby enhancing productivity and competitiveness.